2000
DOI: 10.1128/jvi.74.13.6045-6049.2000
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of Autoantibody-Mediated Hemolytic Anemia by Viral Infection

Abstract: Strong enhancement of the pathogenicity of an antierythrocyte monoclonal antibody was observed after infection of mice with lactate dehydrogenase-elevating virus. While injection of the antierythrocyte antibody alone induced only moderate anemia, concomitant infection with this virus, which is harmless in most normal mice, led to a dramatic drop in the hematocrit and to death of infected animals. In vitro and in vivo analyses showed a dramatic increase in the ability of macrophages from infected mice to phagoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 37 publications
3
33
0
Order By: Relevance
“…Therefore, it is not caused by new antibody production in response to infection, because such antibody responses are T-cell dependent and do not start before 4 days after infection, 14 and antigenic mimicry cannot explain this virally induced platelet drop. Because LDV may enhance phagocytosis, 15 it could be postulated that the virus induces thrombocytopenia by this mechanism. Indeed, treatment with clodronate-containing liposomes indicated that the enhancing effect of LDV on autoantibody-dependent thrombocytopenia involves phagocytosis exclusively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not caused by new antibody production in response to infection, because such antibody responses are T-cell dependent and do not start before 4 days after infection, 14 and antigenic mimicry cannot explain this virally induced platelet drop. Because LDV may enhance phagocytosis, 15 it could be postulated that the virus induces thrombocytopenia by this mechanism. Indeed, treatment with clodronate-containing liposomes indicated that the enhancing effect of LDV on autoantibody-dependent thrombocytopenia involves phagocytosis exclusively.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] However, in the primary form of AIHA, no inciting cause is identified. 7 The basic pathogenesis of primary AIHA is poorly understood, but clearly results from a failure of tolerance mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, mouse infection with lactate dehydrogenase-elevating virus (LDV) strongly enhances the pathogenicity of both anti-erythrocyte and anti-platelet IgG autoantibodies, leading to severe anemia and thrombocytopenia, respectively (18)(19)(20). This effect of the infection is mediated by an increased phagocytosis activity of macrophages (18,19), resulting from IFN-g secretion by NK cells (21)(22)(23). However, a relationship between inflammatory cytokine secretion and autoantibody-mediated mouse thrombocytopenia has not been observed in all experimental models (24).…”
mentioning
confidence: 99%